Paradigma Hermeneutika Feminis Amina Wadud - Budi, Eko Prasetyo; Amalia, Rosyida (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
Starting from the background of gender issues in the study of modern interpretation, verses that are understood as textual give rise to gender bias and trigger a long debate between patriarchs and feminists. This paper aims to unravel Amina Wadud's interpretation in terms of her thoughts and interpretation methodology used to understand the messages in the Qur'an. By using a qualitative research type with a descriptive approach method, this study reveals a deeper meaning that patriarchal bias must be abolished and replaced with the concept of gender equality where women also have the same rights as men. The results of the study show that Amina Wadud does not only carry out textual interpretation of verses, but assesses several views from classical interpretation, including, first, QS. Al-Baqarah 228, the explicit content of this verse is equality that is built on mutual agreement by considering the principles of mas'uliyah. Second, QS. Al Nisa: 36, regarding polygamy which includes three contexts, namely: economic context, reproductive context, and biological context. Then QS. An-Nisa: 34, that men and women are equal in all respects according to their respective portions.